Handbook of immunosenescence basic understanding and clinical implications - Fulop, Tamas; Franceschi, Claudio; Hirokawa, Katsuiku; Pawelec, Graham (Springer, 2019)
Immunosenescence is an imprecise term used to describe deleterious age-associated changes to immune parameters observed in all mammals studied so far. It represents a rapidly progressing science in the aging field, with a vertiginous volume of new data, knowledge and concepts concerning these changes. We are poised to be in a position to translate these accumulated data into the clinical setting via better understanding of the contribution of immunosenescence to age-associated pathologies, and their prevention by appropriate interventions. This authoritative handbook seeks to encompass the current state of our knowledge on the multitude of those changes to immunity related to aging, with contributions from experts in the research and clinical areas. This book therefore considers methods and models for studying immunosenescence; cellular immunosenescence of T cells, B cells, neutrophils, antigen presenting cells, NK, NKT and stem cells; genetics; mechanisms including receptors and signal transduction; mitochondria; proteasome; cytokines; neuro-endocrine-immune networks; inflammation; thymus; clinical relevance in disease states including infections, autoimmunity, cancer, metabolic syndrome, neurodegenerative diseases, frailty and osteoporosis; modulation by nutrition, lipids, vaccination and the question "can interventions to influence immunosenescence be realistically proposed based on our current state of knowledge?
"With 272 figures and 112 tables" -- Titelseite
Second edition in 3 Bänden (1st edition 2009 in nur 2 Bänden erschienen)
Keywords: Medicine; Immunology; Geriatrics; Biomedicine